2014
DOI: 10.2174/0929867321666140916113443
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activities of Flavonoids: Structure-Activity Relationship and Mechanism

Abstract: Flavonoids are well known as antibacterial agents against a wide range of pathogenic microorganism. With increasing prevalence of untreatable infections induced by antibiotic resistance bacteria, flavonoids have attracted much interest because of the potential to be substitutes for antibiotics. In this review, the structure-relationship of flavonoids as antibacterial agents is summarized, and the recent advancements on the antibacterial mechanisms of flavonoids are also discussed. It is concluded that hydroxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
369
1
34

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 580 publications
(486 citation statements)
references
References 122 publications
16
369
1
34
Order By: Relevance
“…The outer membrane of gramnegative bacteria is rich in lipopolysaccharide, lipoprotein and phospholipids, which function as a potential barrier to prevent foreign molecules from entering the cell, and enzymes existing in the periplasmic space can break down foreign molecules (Negi, Jayaprakasha, & Jena, 2003;Nikaido, 1994;Russell, 1991). Therefore, compared to gram-negative bacteria, polyphenols can more easily damage the single-layer cell wall to enter the cytoplasm of gram-positive bacteria, probably leading to the inhibition of bacteria nucleic acid synthesis, energy metabolism, and other biological functions (Xie, Yang, Tang, Chen, & Ren, 2015). Besides the factor of bacteria, different polyphenols might have distinct antibacterial effects on gram-positive and gram-negative bacteria.…”
Section: Antibacterial Effects Of 28 Pigmented Bean Coat Extractsmentioning
confidence: 99%
“…The outer membrane of gramnegative bacteria is rich in lipopolysaccharide, lipoprotein and phospholipids, which function as a potential barrier to prevent foreign molecules from entering the cell, and enzymes existing in the periplasmic space can break down foreign molecules (Negi, Jayaprakasha, & Jena, 2003;Nikaido, 1994;Russell, 1991). Therefore, compared to gram-negative bacteria, polyphenols can more easily damage the single-layer cell wall to enter the cytoplasm of gram-positive bacteria, probably leading to the inhibition of bacteria nucleic acid synthesis, energy metabolism, and other biological functions (Xie, Yang, Tang, Chen, & Ren, 2015). Besides the factor of bacteria, different polyphenols might have distinct antibacterial effects on gram-positive and gram-negative bacteria.…”
Section: Antibacterial Effects Of 28 Pigmented Bean Coat Extractsmentioning
confidence: 99%
“…They represent an exceptional class of structural templates that exhibits a wealth of biological functions, which include anti-inflammatory, antioxidant, anti-microbial and anti-tumor activity. Excellent and comprehensive overviews over pharmacological activities of chalcones are given elsewhere (Batovska and Todorova, 2010;Dimmock et al, 1999;Orlikova et al, 2011;Sahu et al, 2012;Xie et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that the antibacterial activities of natural products are related to structures and cellular membranes of tested bacteria by varied mechanisms via several events at a cellular level [62] [63]. Previous study showed a strong relationship between flavonoids structures due to the substitutions on the aromatic rings and antibacterial activity [64]. The exact mode of action mechanism of natural antimicrobials is still not fully understood.…”
Section: Discussionmentioning
confidence: 99%